Pengendalian Kecepatan Motor Dc Secara digital dengan komputer ibm pc menggunakan sensor posisi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Controlling DC motor digitally is an interesting option when complex movement of DC motor is required. This research investigate the performance of home-made digital controller just based on position feedback using PC as the controller. Computer capability to derive speed from position might be applied for controlling motor speed based on position feedback PID control action to control motor position and speed was observed. A pair of optocoupler -placed in such away that a pulse is generated each time the motor rotates 10 degrees- is used to sense position Motor speed is calculated by measuring the period of two pulses. Motor power supply energy was manipulated by switching on and off the power line. PID control action is applied to determine the on period and the off period For position control, control performance is very good by P and I control action the required position is reached in short time without resetting the P and I parameter. For speed control, P and I control action is satisfying if the required speed does not much differ with the speed used to set the P1D parameters, otherwise the P and I parameter must be reset to get optimum control.